Healthcare system performance improvement: A comparison of key policies in seven high-income countries. Issue 1 (11th March 2014) - Gauld, Robin; Burgers, Jako; Dobrow, Mark; Minhas, Rubin; Wendt, Claus; B. Cohen, Alan; Luxford, Karen
Abstract : Purpose: – Evidence suggests that healthcare system performance may be improved with policy emphasis on primary care, quality improvement, and information technology. The authors therefore sought to investigate the extent to which policy makers in seven countries are emphasizing these areas. Design/methodology/approach: – Policies in these three areas in seven high-income countries were compared. A comparative descriptive approach was taken in which each of the country-specialist authors supplied information on key policies and developments pertaining to primary care, quality improvement and information technology, supplemented with routine data. Findings: – Each of the seven countries faces similar challenges with healthcare system performance, yet differs in emphasis on the three key policy areas; efforts in each are, at best, patchy. The authors conclude that there is substantial scope for policy makers to further emphasize primary care, quality improvement and information technology if aiming for high-performing healthcare systems. Originality/value: – This is the first study to investigate policy-makers' commitment to key areas known to improve health system performance. The comparative method illustrates the different emphases that countries have placed on primary care, quality improvement and information technology development.